Câncer infantil: a realidade vivenciada na percepção do cuidador familiar. - Amador, Daniela Doulavince (2011)
The increase in the survival of children with cancer has led the assistance into the context of the experience and needs of the child and the family, who experience the severity of the disease. The objective understand the experiences of family caregivers in the care with a child with cancer. Theoretically, this study is supported by the concept of the family-centered care in the perspective to understand the family carer‟s experience toward an efficient care of the family. It is a qualitative research, whose empiric material was collected throughout interviews recorded from February through April 2011, involving family carers of children with cancer, who were guests at the Casa da Criança institution. The analysis was accomplished as per the theoretical analytical referential of the Analysis of the Discourse, French line, under two discursive formations: to be family carer of a child with cancer, dealing with the unknown, and the family carer facing the child‟s cancer. The findings pointed out to the legates of devotion, abnegation and moral obligation that he imposes on himself in the socio-cultural nuances sustaining the care. In the first discursive formation, it was possible to apprehend the carer‟s conception of care, being seen as an ambiguous form of a gift of God, but also as an obligation that he imposes on himself to be the sole child‟s protector. It was also possible to apprehend the feelings experienced by the carer, in which the suffering starts as from the journey in search of the diagnosis, with failures in the organization and resolution of the services, whilst permeated by the stigma that the cancer represents, implicating in sentiments of blame and fear of the child‟s death. In the second discursive formation, it was possible to go into the family relationships involving the carer, which led us into perceiving that he resents needing to resign from home and the care with the family nucleus, but who suffocates the contact and the support to the large family, so evidencing the fragile ties in this ambience. As regards the strategies of facing, it was possible to observe in the discourses that the carers get hold of a strength and courage to struggle for the child‟s life that they themselves never thought they had, further to being supported by faith, religiousness and spirituality. The network that offers social support to the carer is formed by family care institutions. The meanings that the families attribute to their experiences widen the understanding of the concepts of the family-centered care, there allowing a way toward the reflection and the practical applicability of approach. As from the analyzed factors, we detach a few aspects that need be considered by the nurse who deals in the assistance to children with cancer and their families: the importance of an efficient dialogical relationship to allow a family member to expose his feelings and to make him feel comfortable with the care-rendering institutions; the incentive to face the cancer in family, cutting off the carer‟s overload; understanding the vulnerability of the carer who needs to be thoroughly assisted and the need to strengthen the facing strategies used by the carer.